EP1217 Surgical staging prior to chemoradiation is beneficial for survival in patients with high stage cervical cancer. (1st November 2019) - Kenter, G; Popovic, M; Alran, S; Fourchotte, V; Dureau, S; Mandic, A; Zijlmans, H; Hillemans, P; Lecuru, F; Ngo, C; Wimberger, P; Rouzier, R; et al.
Abstract : Introduction/Background: The RAIDs consortium (http://www.raids-fp7.eu/) conducted a prospective study [BioRAIDs (NCT02428842 )] with the objectives to stratify patient populations as well as to identify clinical and molecular patterns associated with poor outcome. Debate is ongoing about the benefit of surgical staging prior to chemoradiation. Here we report on the value of diagnostic pelvic and para-aortal lymphadenectomy (LA) for patients scheduled for primary chemoradiation. Methodology: Between 2013–2017, the RAIDs Network collected a clinical dataset involving 419 participant patients from 18 centers in seven EU countries, of whom 377 patients are evaluable. Treatment decisions had been based on guidelines defined in the clinical protocol as detailed in Ngo et al, 2015 and were also based on the policy of the center. Systematic MRI imaging was mandatory. LA as well as PET imaging was recommended. From 262 patients in stage IIB-IV who were scheduled for primary chemoradiation 126underwent LA. Results: Patients who underwent surgical LA followed by chemoradiation showed better PFS at 24 months compared to those who did not. This difference was statistically significant (p-value of univariate : p=0.008). If we adjust with the FIGO, the effect of staging LA remains. Conclusion: Although these data were collected retrospectively and might be biased we found that staging LA improved PFS also after adjusting for stage. These data are in line with literature and advocate for a randomized trial to proof the value of staging lymphadenectomy prior to chemoradiation for patients with high stage cervical cancer. Disclosure: This project has received funding from the European Union's Seventh Program for research, technological development and demonstration under grant agreement No 30481.